2015
DOI: 10.15537/smj.2015.11.13604
|View full text |Cite
|
Sign up to set email alerts
|

Decline in menarcheal age among Saudi girls

Abstract: Objectives:To estimate age at menarche and to assess trends in menarcheal age among Saudi women.Methods:A prospective longitudinal study was conducted among healthy prepubertal female school children and adolescents from September 2006 to July 2012 in Riyadh, Kingdom of Saudi Arabia. Study participants were invited from diverse socioeconomic backgrounds. Tanner stage, height, weight, body mass index, and socioeconomic parameters including parent’s level of education were collected. Age at menarche was compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…27 In a study conducted by Al Alwan et al in Saudi Arabia. 28 , the mean AOM was 13.08±1.10 years, and the mother's menarcheal age was 13.67±1.40 years. It has been shown that girls experience menarche at an earlier age than their mothers.…”
Section: Discussionmentioning
confidence: 97%
“…27 In a study conducted by Al Alwan et al in Saudi Arabia. 28 , the mean AOM was 13.08±1.10 years, and the mother's menarcheal age was 13.67±1.40 years. It has been shown that girls experience menarche at an earlier age than their mothers.…”
Section: Discussionmentioning
confidence: 97%
“…These results are similar to those of other studies conducted on the age at first menstruation in Saudi Arabia. For example, a study conducted in Riyadh found that the mean age at the first menstruation was 13.08 ± 1.1 years old [ 32 ]. The findings of the current study are consistent with those reported in studies conducted in various regions, including Nepal [ 33 , 34 ], the USA [ 35 ], Greece [ 36 ], and France [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Menarche is the first step of the transformation of a girl to a woman 1 and an important event for each female as it marks the beginning of her adulthood with all its known biological and psychological consequences. 2 The normal mean age of menarche varies substantially between women across different countries and ethnic groups. 3 The recorded mean menarche age in Jordan was 13.1 years, 14.8 years in Ethiopia, 12.5 years in Ghana, and 12.31 years in Croatia.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, the age of puberty becomes important due to the increased recognition of the association between early menarche and the future development of breast cancer and cardiovascular diseases in adulthood. 2 There is a change in the trend of menarche in different parts of the world. It tends to occur earlier among girls in the United States and Europe than in the past decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation